2005
DOI: 10.1097/01.mop.0000147905.92602.bb
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic shoulder dislocation in the adolescent athlete: advances in surgical treatment

Abstract: Conservative management of traumatic shoulder dislocations in young patients is associated with high rates of recurrent instability. Recent studies have demonstrated improved results and significant reduction in recurrent instability in patients treated with surgical stabilization when compared with nonoperative treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
30
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 15 publications
1
30
0
1
Order By: Relevance
“…Young contact sport athletes represent cases with high rates of recurrence for instability surgery. [26][27][28][29] Our sample includes many of these with evidence of multiple dislocations and subluxations, many with multiple surgeries already when participating in highrisk sports.…”
Section: Discussionmentioning
confidence: 99%
“…Young contact sport athletes represent cases with high rates of recurrence for instability surgery. [26][27][28][29] Our sample includes many of these with evidence of multiple dislocations and subluxations, many with multiple surgeries already when participating in highrisk sports.…”
Section: Discussionmentioning
confidence: 99%
“…24 Athletes participating in collision sports (eg, football and rugby) and contact sports (eg, wrestling and basketball) are at a notably high risk for injury. 7,10,1820,27 Recurrent dislocation is common in this population, particularly in young athletes where the reported rate of recurrence after arthroscopic Bankart repair ranges from 5.1% to 31%. 4,6,8,9,14,15,18,20,32 …”
mentioning
confidence: 99%
“…Recent studies have reported decreased rates of recurrent instability and improved outcomes in patients treated with surgical stabilization. 4,10,16 More recent studies have focused on the outcomes of arthroscopic anterior stabilization in adults using validated shoulder outcome scores. Milchteim et al 22 examined the results of arthroscopic Bankart repair using suture anchors in 89 highly active patients with a mean age of 21.9 years.…”
Section: Discussionmentioning
confidence: 99%
“…24 Athletes participating in collision sports (eg, football and rugby) and contact sports (eg, wrestling and basketball) are at a notably high risk for injury. 7,10,[18][19][20]27 Recurrent dislocation is common in this population, particularly in young athletes where the reported rate of recurrence after arthroscopic Bankart repair ranges from 5.1% to 31%. 4,6,8,9,14,15,18,20,32 However, a review of the literature on collision and contact athletes revealed that the majority of these included heterogeneous patient populations and have combined adult and adolescent athletes.…”
mentioning
confidence: 99%